2004
DOI: 10.1017/s0950268804002675
|View full text |Cite
|
Sign up to set email alerts
|

Estimating transmission parameters of F4+ E. coli for F4-receptor-positive and -negative piglets: one-to-one transmission experiment

Abstract: SUMMARY F4+Escherichia coli is an important agent of post-weaning diarrhoea in piglets. Piglets that express an adhesion site for F4+ E. coli in their small intestine (F4R+) shed higher numbers of F4+ E. coli than piglets lacking this site (F4Rx). We hypothesized that F4R+ piglets are more infectious and more susceptible for F4+ E. coli. This implies that in populations with F4R+ and F4Rx piglets, the transmission would be dependent on the frequency of both types of animals. To quantify the difference in infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…F4R+ piglets were more susceptible to F4+ E. coli infection than F4Rx piglets, but were not more infectious. This confirms and completes the findings of a one-to-one transmission experiment [12] in which susceptibility was found to differ, but which was inconclusive on the infectiousness as none of the inoculated F4Rx piglets became infectious. In the current study, six F4Rx piglets did become infectious, four inoculated and two contact piglets.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…F4R+ piglets were more susceptible to F4+ E. coli infection than F4Rx piglets, but were not more infectious. This confirms and completes the findings of a one-to-one transmission experiment [12] in which susceptibility was found to differ, but which was inconclusive on the infectiousness as none of the inoculated F4Rx piglets became infectious. In the current study, six F4Rx piglets did become infectious, four inoculated and two contact piglets.…”
Section: Discussionsupporting
confidence: 86%
“…Results of a one-to-one transmission experiment with F4+ E. coli showed that F4Rx piglets were less susceptible for F4+ E. coli infection than F4R+ piglets [12]. Results of this experiment were inconclusive on whether F4R+ and F4Rx piglets differed in infectiousness, as none of the inoculated F4Rx piglets was infectious, probably due to a low infection pressure.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…F 4+E-coli can attach to the microvilli of the small intestine enterocytes, where they produce enterotoxins. These toxins affect the enterocytes and cause increased secretion of fluid, leading to diarrhoea, dehydration, acidosis, or in some cases, even to death (Geenen, 2005;Geenen et al, 2004Geenen et al, , 2007. To this day, several empirical studies have investigated how the occurrence of clinical symptoms depends on environmental factors, such as weaning age, diet composition, temperature or litter size Carstensen et al, 2005;Pluske et al, 2007;Wellock et al, 2006), or the genetic aspects of intestinal infections (Melin et al, 2004;Zhang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%